Analisis Semiotik dalam Kumpulan Cerita Pendek Kidung Penjaga Malam Karya Mim Yudiarto : Semiotic Analysis in the Short Story Collection Kidung Penjaga Malam by Mim Yudiarto - Sulmayanti, Indah; Harahap, Rosminah; Safitri, Dwi Alidya; Sofiana, Zulfa (Universitas Tidar, 2025)
This study aims to examine the latent structures of meaning embedded in the short story collection Kidung Penjaga Malam by Mim Yudiarto using a structural semiotic approach. The stories in this collection do not merely present horror or mystery narratives, but they also embed various symbols, myths, and local cultural elements that invite deeper interpretation. This research applies a qualitative descriptive method with a semiotic text analysis approach. The analysis focuses on the five semiotic codes originally proposed by Roland Barthes, updated through contemporary structural semiotic frameworks: hermeneutic (enigma), proairetic (action), semic (connotation), symbolic (binary opposition), and cultural (referential) codes. Data were obtained through close reading and note-taking of sign systems within the stories, which were then classified and interpreted through this theoretical lens. The results show that the narrative structures in these stories are constructed through layered and complex sign strategies. Elements such as birdsong, spiritual chants (kidung), mirrors, and character expression’s function both as atmospheric tools and as representations of the characters’ internal states. Furthermore, the characters' actions are found to be not merely narrative drivers, but also carriers of moral and spiritual values rooted in local traditions. From a cultural perspective, the stories also reflect rituals, Javanese myths, and customary norms that remain relevant in contemporary society. The conclusion of this study affirms that Kidung Penjaga Malam is a literary work that succeeds aesthetically and semiotically in constructing rich narrative layers, while also reflecting the spiritual, social, and psychological anxieties of today’s society. The symbols and codes scattered throughout the stories not only enhance the mysterious atmosphere but also open space for critical readings that connect the text to broader cultural and ideological contexts.